The beauty and the sorrow an intimate history of the First World War - Englund, Peter 1957-
Englund examines the history of World War I through the experiences of the average man and woman-- not only the tragedy and horror but also the absurdity and even, at times, the beauty. In a brilliant mosaic of perspectives that moves between the home front and the front lines, he reconstructs the feelings, impressions, experiences, and shifting spirits of twenty particular people, allowing them to speak not only for themselves but also for all those who were in some way shaped by the war, but whose voices have been forgotten, rejected, or simply remained unheard